Synthesis, structure, and properties of the high Nb–TiAl alloy after Ni coatings by plasma surface alloying technique. (February 2020) - Wang, Y.R.; Zheng, K.; Wang, R.Y.; Hei, H.J.; Wang, Y.S.; Gao, J.; Liang, Y.F.; Ma, Y.; Zhou, B.; Yu, S.W.; Tang, B.; Wang, Y.L.; et al.
Abstract: Ni coatings were prepared on the high Nb–TiAl alloy by the plasma surface alloying technique. The results found that surface morphology and microstructure exhibited a strong dependence on the deposited temperature. The elements diffusion during the metalizing stage leaded to the high hardness value and adhesion force between the Ni coating and substrate. The corrosion resistance of the Ni-coated specimens depended on the fabrication temperature related to the deposition and diffusion layers. For the oxidation, the weight gain rate was involved in the chemical reaction in the initial oxidation stage. The inter-diffusion among elements such as the nickel, titanium, and aluminum resulted in the high adhesion force after the oxidation, improving the bonding force between the Ni coating and substrate. Highlights: Ni-coatings were prepared on Ti–45Al-8.5Nb substrate by plasma alloying technique. Surface morphology and microstructure exhibited a strong dependence on the deposited temperature. Ni-coatings presented the considerable corrosion resistance. Ni-coatings displayed the good adhesion force before and after oxidation caused by the metallurgical bonding.